First results of permafrost monitoring on the cryospheric site of Russian scientiﬁ c center on Spitsbergen (RSCS) - N. E. Demidov; S. R. Verkulich; E. S. Karaevskaya; A. L. Nikulina; L. M. Savatyugin; Н. Э. Демидов; Е. С. Караевская; С. Р. Веркулич; А. Л. Никулина; Л. М. Саватюгин (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2016)
The system of long-term permafrost observations was organised on the cryospheric site of Russian Scientiﬁ c Center on Spitsbergen in summer 2016. The monitoring site is established in the vicinity of mining settlement Barentsburg on a sequence of Holocene marine terraces. The core drilling showed that the thickness of gravel sands and clays with massive and schlieren cryostructure forming the accumulative terraces is of 2–7 m. Cretaceous and Neocene fractured sandstones and mudstones underlie them. Automated thermistor cables were installed in two boreholes to monitor the temperature on the depth of zero annual amplitude and seasonal distribution of zero-degree isotherm. The temperature –2,37 °C was measured at 15 m depth. The thickness of active layer measured at ten meter net on the observational site of 100100 m varied from 1,15 to 2,60 m with average of 1,56 m. Chemical analysis of aqueous extract revealed a geochemical barrier at 0,8–1,6 m below permafrost upper boundary in the period of maximum thawing, which apparently marks maximum seasonal thaw depth during the Holocene climatic optimum. In this paper recommendations on continuing and extending of pilot permafrost dynamic observations on Spitsbergen are given. В 2016 г. на криосферном полигоне РНЦШ (о. Западный Шпицберген) впервые начаты долговременные наблюдения за состоянием мерзлых пород. Полигон расположен в окрестностях пос. Баренцбург на типичной для побережья Шпицбергена лестнице голоценовых морских террас. Согласно результатам проведенного колонкового бурения мощность гравелистых песков и суглинков с массивной и шлировой криотекстурой, слагающих аккумулятивные террасы, варьирует от 2 до 7 м; ниже залегают меловые и неогеновые трещиноватые песчаники и сланцы. Две скважины оборудованы автоматическими термометрическими косами для мониторинга температуры на глубине нулевых амплитуд и сезонного проникновения в грунт нулевой изотермы. Температура на глубине 15 м составила –2,37 °С. Измерения мощности сезонно-талого слоя, проведенные в сентябре по ...